Students’ Reaction on Operating Rhetorical Strategies in Promoting Linguistic Skills and Cultural Diversity at Islamic Multicultural Classrooms - Dwi Astuti Wahyu Nurhayati (Dinamika Ilmu, 2023)
This research was motivated by some multicultural classroom students’ reactions to practicing writing argumentative text including the fact that Indonesia's adult literacy rate of 95% is not accompanied by the ability to recognize and adopt composed facts, which on average is very little. This research was formerly aimed to depict how multicultural classroom students react to deploying rhetorical strategies to write and advance their linguistic skills as well as cultural diversity The research approach adopted in this research was qualitative. The types of data sources in this study are documents in the form of various thesis manuscripts from a multicultural classroom of Masters’s Study programs at UIN SATU Tulungagung. The data collection technique applied to the main data source in the form of archives or written documents is to rely on the note-taking technique and administrating one online questionnaire survey to thirty-two students as well as attending an interview. In the thesis of multicultural classroom deployed seven strategies counting definition, comparison, cause-and-effect, problem-solution, means-end, listing, partition strategies were applied by students in argumentative text units which they compiled at various levels, both at the sentence unit level, paragraph unit, and essay unit; several facets of appealing the students experience in writing argumentative text also appeared promoting linguistic and cultural diverse in composing argumentative text counting 5 linguistics facets and 2 cultural diverse such as argumentative state/disputatiousness, probing and assortment criticism, adopting composing typical, recognized arrangement, pondering on preceding insight, instructors’ concentrating on awareness development, indigenous upbringing; experience of deploying rhetorical strategies in order to enhance linguistic skill counting conceptual and procedural knowledge to the same degree credibility, logic and emotion mainly deploying cognitive, social, search and metacognitive strategies.